Perbandingan Efektivitas Produk Filgrastim pada Pasien Keganasan Limfoma yang Menerima Kemoterapi di RSUP dr. Sardjito Yogyakarta - Setiani, Dhien; Ikawati, Zulies; Widayati, Kartika (Jurnal Farmasi (Journal of Pharmacy), 2015)
Neutropenia is a common toxicity in cancer patients receiving chemotherapy myelotoxic as lymphoma result. Granulocyte Colony Stimulating Factor (G-CSF) is clinically recommended for neutropenia. Filgrastim is a generic name of the brand G - CSF products circulating in Indonesia such as Filgrastim brand A and brand B produced by a different manufacturer. The differences Filgrastim brand A and brand B produced by non-factory is that Filgrastim A product’s price is cheaper than brand B. Comparison of the effectiveness of Filgrastim brand A and brand B in patients at DR.Sardjito Hospital Yogyakarta need to be examined to evaluate the effectiveness of the type of drugs has been clinically used. The purpose of this study was to compare the effectiveness of Filgrastim A and B on the use of daily clinical practice at RSUP Dr. Sardjito Yogyakarta. The design of this study is analytic retrospective cohort study that is applied for patients receiving chemotherapy in cancer Installation Tulip Hospital Dr. Sardjito. Data was retrieved from medical records the period January 2013 to March 2015. Comparison of the effectiveness of filgrastim uses the parameter of time to reach the Absolute Neutrophil Count (ANC) recovery. Data of characteristics subjects were analyzed by using chi square Goodness of Fit for categorical data and independent t test for numerical data. The comparison of effectiveness of filgrastim was analyzed by using survival analysis. A total of the study showed that there were 80 subjects which consists of 192 episodes of neutropenia incidence of filgrastim therapy. From 80 subjects, there were 43 subjects ( 53,5 % ) which consist of 72 episodes of neutropenic (33 episodes with filgrastim brand A and 39 episodes with filgrastim brand B) that met the inclusion criteria. The result of the comparison of filgrastim effectiveness based on time to ANC recovery, according to the bivariate Kaplan-Meier with the laboratory observation data 24 hours post last injections, it shows that Filgrastim brand A has a median recovery time faster than Filgrastim brand B (1,00 vs 2,00 p< 0,05). The conclusions of this study , in the ANC recovery time, Filgrastim brand A more effective than Filgrastim brand B.